STRATEGI EDUKASI MASYARAKAT DALAM MENANGGULANGI DAMPAK JUDI ONLINE DAN PENYALAHGUNAAN NARKOBA DI DESA HUTA TINGGI, KECAMATAN PUNCAK SORIK MARAPI, MANDAILING NATAL - Asrofi Asrofi; Anriyan Makmur Matondang; Risky Aulia Nasution; Rahmadani, Riski; Inkrid Alia; Yusni Zakiah Lubis; Dina Dwi Putri; Ananda Aulia Putri; Alvini Riska; Mhd Raihan Lubis (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The phenomenon of increasing cases of online gambling (judol) and drug abuse among the community, especially the younger generation, poses a serious threat to the future of the nation. This community service program aims to identify the root causes of the problem and raise public the people of Huta Tinggi Village of the social, economic, and psychological impacts of both issues. Through an educational approach, field observations, and interactive dialogues, this initiative targets vulnerable groups such as teenagers, students, and parents. The results of the initiative indicate that low digital literacy, weak family supervision, and a lack of productive spaces are key factors driving high levels of community involvement in online gambling and drug abuse. Additionally, easy access to the internet and unrestricted social interactions accelerate their spread. The persuasive education provided has proven effective in fostering new awareness within the community. The initiative also involves local religious leaders and youth to strengthen the sustainability of positive messages. It is hoped that these efforts will serve as the first step toward building family- and community-based social resilience. Thus, addressing the dangers of gambling and drugs is not merely reactive but also preventive and sustainable.